(untitled) (Academic Journal of Internal Affairs, 2019)
The author gives a comprehensive evaluation of the new Hungarian Code of Criminal Procedure (Act No. XC. of 2017). He concludes that in contrast to previous codes of procedure the new law does not reflect any particular ideology; it rather resembles a manual that instructs officials on how to bring a case to completion. Some procedural arrangements are in line with victim centered criminal policy.